Pemanfaatan Teknologi Budikdamber (Budidaya Ikan di dalam Ember) Sebagai Model Urban Farming Berkelanjutan - Muhammad Marzuki; Bagus Dwi Hari Setyono; Laily Fitriani Mulyani; Andre Rachmat Scabra (Universitas Mataram, 2022)
Fish is a food of high quality and is very beneficial for the health of the body. The various benefits of fish meat will only be obtained if the fish consumed is fresh. In conditions that are not fresh (rotten), the nutritional content in fish meat is damaged. One of the efforts that can be done so that the consumption of fresh fish can be carried out continuously is to carry out urban farming activities, namely the cultivation of fish in buckets (budikdamber). This community service activity aims to increase knowledge and provide technical guidance to partners involved in the application of bucket fish cultivation technology. This community service activity is carried out through various methods of structured activities, namely site surveys, preparation of socialization materials and technical guidance for activities, formation of technology models, technical implementation assistance, and evaluation. The activity was carried out in